Exploring low ability and disaffected pupils’ perceptions of the relevance of design and technology : a case study with a group of pupils aged between 14 and 16, Key Stage 4 - Thomas, Mike; Denton, Howard (Design and Technology Education: An International Journal, 2008)
This paper describes a case study carried out to establish a group of low ability and disaffected pupils’ perception of the term ‘relevance’ with particular reference to design and technology. Discussion of the relationship between pupils’ perceived relevance of an activity and their levels of engagement has appeared on the UK educational agenda, (Ofsted 2005, 51-52, Davies et al, 2004, 147, Daniels et al 1998, 5.5, Denton, 1992), but not with the frequency which might be expected. Initial research suggested that pupils at this school had a very positiveperception of the ‘relevance’ of design and technology. In contrast the literature reviewed suggested that pupils in their samples had a low perception of the ‘relevance’ of design and technology. The findings suggest a dualunderstanding of ‘relevance’: in terms of present/situational and in terms of preparation for a particular purpose. The group of pupils in this research perceived ‘relevance’ more in terms of present/situational, and the implications of this finding for educational practitioners and other stakeholders is discussed.